2019
DOI: 10.3892/or.2019.7287
|View full text |Cite
|
Sign up to set email alerts
|

WT1 regulates cyclin�A1 expression in K562�cells

Abstract: The restricted expression of Wilms tumor 1 (WT1) and cyclin A1 (CCNA1) in normal tissues, as opposed to their abnormal expression in leukemia demonstrates the applicability of WT1 and CCNA1 as cancer antigens for immunotherapy, and as markers for prognosis and relapse. In this study, the WT1 and CCNA1 mRNA levels were found to be elevated in bone marrow samples from pediatric acute promyelocytic leukemia (APL or AML-M3) patients, and to be quite varied in pediatric acute lymphocytic leukemia (ALL) patients, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Studies have shown that WT1 is overexpressed in various hematological malignancies, such as aplastic anemia [10] and leukemia [11], but its expression in AML and its role in the classification of AML are still controversial. In this study, real-time quantitative PCR was used to analyze the relative expression of WT1 mRNA in bone marrow samples of 121 AML patients and nine non-leukemia patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that WT1 is overexpressed in various hematological malignancies, such as aplastic anemia [10] and leukemia [11], but its expression in AML and its role in the classification of AML are still controversial. In this study, real-time quantitative PCR was used to analyze the relative expression of WT1 mRNA in bone marrow samples of 121 AML patients and nine non-leukemia patients.…”
Section: Discussionmentioning
confidence: 99%